Analisis Segmentasi Pasar Terhadap Loyalitas Konsumen (Studi Kasus Kedai My Cake Pekkabata, Kec. Duampanua, Kabupaten Pinrang) - Sy.Fathya Farhana; Nurhapsa Nurhapsa; Irninthya Nanda Pratami Irwan (Jurnal Agribis, 2024)
The title of this research is Market Segmentation Analysis on Consumer Loyalty (Case Study of My Cake Shop Pekkabata, Duampanua District, Pinrang Regency). The cake is a food commonly consumed by the community, namely dough consisting of flour, eggs, sugar, raising agents, and milk. It can usually be decorated with buttercream, chocolate, and so on. Currently, cakes sold on the market have different shapes, qualities, and tastes. The more the era develops, the more technology, equipment, knowledge, and materials are used to develop. The objectives of this study are: 1. To determine the partial significant influence of consumer behavior, demographic, and psychographic factors on consumer loyalty at My Cake Shop. 2. To determine the simultaneous significant influence of behavioral, demographic, and psychographic factors on consumer loyalty at My Cake Shop. The sampling method uses (purposive sampling) with certain considerations and criteria. The data collection methods in this study are observation, questionnaires, and documentation. Instrument testing is done by testing the validation and reliability using the SPSS version 26 program and analyzed using multiple linear regression analysis techniques. So the results of the study indicate that market segmentation of consumer loyalty at My Cake Shop consisting of demographic, psychographic, and behavioral variables has a significant effect partially, and consumer loyalty variables simultaneously have an effect on consumer loyalty at My Cake Shop.